A method for preparing wear-resistant high-strength plastic

By mixing the matting agent with elastic polystyrene and combining wear-resistant agents, wear-resistant high-strength plastics with matting and impact resistance, the problems of brittle fracture and high gloss of polystyrene plastics are solved, and the materials are realized Improves wear resistance and aesthetics.

CN117964985BActive Publication Date: 2024-12-13GUANGDONG JUBANG XINGCAI TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311737175.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-21
Publication Date
2024-12-13
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

Polystyrene plastics are prone to brittle fracture under external stress, affecting their service life. At the same time, their high gloss leads to glare, affecting aesthetics and appearance, and in some occasions, extinction effect is required.

Method used

The impact-resistant base material is used to mix the matting agent and elastic polystyrene to make wear-resistant high-strength plastic. The matting agent is spinning, etching and shearing to make the matting staple fiber and para-hydroxybenzaldehyde reacted with pyrrole polyester. Combined with additives such as wear-resistant agents, flame retardants, dispersants, etc., a material with extinction and impact resistance is formed.

Benefits of technology

The impact resistance and extinction effect of plastic is improved, and the diffuse reflection of light is enhanced through the irregular surface and porous structure of the extinction staple fiber, which enhances the wear resistance and aesthetics of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing a wear-resistant high-strength plastic, and relates to the field of plastic technology. The present invention first prepares a matting agent from 1H-pyrrole-3,4-dicarboxylic acid, 1,2,3-tribromopropane, and p-hydroxybenzaldehyde, and constructs a micro-nano rough plane on the plastic surface through a surface containing a cone-shaped protrusion and a porous microsphere fibrous structure, enhances the multiple reflections of light, and synergizes with the light-absorbing structure to make the plastic have a matting effect; after preparing elastic polystyrene from N-allylmaleimide, styrene, and 1,5-hexadiene, the matting agent is reacted to prepare an impact-resistant base material, and the plastic has an impact-resistant effect through the yield deformation effect of the soft phase of the elastic polystyrene and the rigid support effect of the hard phase, the dispersion effect of the matting agent, and the common force effect; the impact-resistant base material is mixed with other additives to prepare a wear-resistant high-strength plastic. The plastic prepared by the present invention has a matting and impact-resistant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, in particular to a method for preparing wear-resistant high-strength plastics. Background Art

[0002] As an indispensable synthetic material in people's production and life, the output of plastics is increasing day by day, which brings convenience to people's lives. Polystyrene plastic refers to a type of plastic containing styrene in the macromolecular chain, and is one of the most widely used general-purpose plastics. The structural characteristics of polystyrene are that the main chain of the macromolecule is a saturated hydrocarbon polymer, and the side group is a large benzene ring, so it has good electrical properties, chemical properties, rigidity, dimensional stability and high hardness. By adding fibrous or other shaped materials (such as glass fiber, polyester fiber, graphite, silicate, etc.), the strength and wear resistance of polystyrene can be improved, making it more durable. However, the rigid and hard characteristics of polystyrene make it easy to break brittlely under external stress, which in turn affects its service life.

[0003] Polystyrene has a high surface gloss and will reflect light, thus producing glare, which will affect the aesthetics and visual experience of plastic products. At the same time, in recent years, low-reflective matte and extinction products have become increasingly popular among consumers. At the same time, in some special occasions, due to aesthetic and technical requirements, certain extinction requirements will be placed on the surface gloss of the products. Summary of the invention

[0004] The purpose of the present invention is to provide a wear-resistant high-strength plastic and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A wear-resistant high-strength plastic is prepared by mixing an impact-resistant base material with other additives; the impact-resistant base material is prepared by a matting agent and elastic polystyrene.

[0007] Furthermore, the matting agent is prepared by spinning, etching and shearing pyrrole-based polyester to obtain matting staple fibers, and then reacting the fibers with p-hydroxybenzaldehyde.

[0008] Furthermore, the pyrrolyl polyester is prepared from 1H-pyrrole-3,4-dicarboxylic acid and 1,2,3-tribromopropane; the spinning, etching and shearing treatments are as follows: after the pyrrolyl polyester is melt-spun to obtain the pyrrolyl polyester monofilament, the pyrrolyl polyester monofilament is self-spinned and irradiated with tantalum ions, and then immersed in an alkali-alcohol mixture for a period of time, and after washing, drying and shearing, a matte staple fiber is obtained.

[0009] Furthermore, the elastic polystyrene is prepared from N-allylmaleimide, styrene and 1,5-hexadiene.

[0010] Furthermore, the other additives include anti-wear agent, flame retardant, dispersant, antioxidant; the anti-wear agent is aluminum oxide powder; the flame retardant is triethyl phosphate; the dispersant is stearic acid; and the antioxidant is tri(2,4-di-tert-butyl)phenyl phosphite.

[0011] Furthermore, a method for preparing a wear-resistant high-strength plastic comprises the following preparation steps:

[0012] (1) Pretreated staple fibers, p-hydroxybenzaldehyde, and pyridine were mixed in a mass ratio of 1:1:15 to 1:3:25, reacted at 200 to 300 rpm and 91 to 95°C for 25 to 35 hours, and then 38% hydrochloric acid was added in an amount 2 to 4 times the mass of the pretreated staple fibers. After ultrasonic treatment at a frequency of 30 to 40 kHz and 95 to 105°C for 30 to 40 minutes, the fibers were washed with ethanol and deionized water for 3 to 5 times in sequence, and dried at 50 to 60°C for 2 to 4 hours to obtain a matting agent.

[0013] (2) N-allylmaleimide, styrene, cyclohexane, and butyl lithium were mixed in a mass ratio of 4:9:500:0.005-6:11:500:0.007, stirred at 200-300 rpm and 60-70°C for 30-50 min, and then 1,5-hexadiene (1.1-1.5 times the mass of N-allylmaleimide) was added. The reaction was continued for 60-90 min, and then N-allylmaleimide was added. Styrene (4-6 times the mass of N-allylmaleimide) and butyl lithium (0.006 times the mass of N-allylmaleimide) are reacted at 200-300 rpm and 75-85°C for 30-50 min, and then anhydrous ethanol (0.010-0.014 times the mass of N-allylmaleimide) is added. After stirring at 100-200 rpm for 10-20 min, the mixture is dried at 80-90°C for 6-8 h to obtain elastic polystyrene.

[0014] (3) Elastic polystyrene and matting agent are mixed in a mass ratio of 60:15-80:15, stirred at 150-170°C and 600-800 rpm for 6-12 hours, and then an additive mixture of 1-2 times the mass of the matting agent is added, wherein the mass ratio of alumina powder, stearic acid, triethyl phosphate and tri(2,4-di-tert-butyl)phenyl phosphite is 0.05:0.6:3:0.03-0.15:0.8:5:0.03, stirred at 100-200 rpm and 190-210°C for 2-4 hours, and extruded and granulated at 190-210°C to obtain a wear-resistant high-strength plastic.

[0015] Furthermore, the method for preparing the pretreated staple fibers in step (1) is as follows: mixing the matte staple fibers, sodium acetate, and deionized water in a mass ratio of 1:0.7:9 to 1:1.4:18, reacting at 95 to 105°C and 200 to 300 rpm for 4 to 6 hours, washing with deionized water for 3 to 5 times, and drying at 45 to 55°C for 2 to 4 hours to obtain the pretreated staple fibers.

[0016] Furthermore, the method for matting the short fibers is as follows: irradiating the pyrrole-based polyester monofilament rotating at 30-50 rpm with tantalum ions at an irradiation density of 10 5 ~10 7 Tracks / cm 2 The irradiated pyrrolyl polyester monofilament was immersed in an alkali-alcohol mixture with a mass fraction of 10 to 20 times that of the pyrrolyl polyester monofilament for 10 to 20 minutes. The mass ratio of the alkali-alcohol mixture was 10% sodium hydroxide solution and methanol was 1:1. The monofilament was washed with deionized water until the pH value of the washing solution was 6 to 7. After drying at room temperature for 12 hours, the monofilament was sheared to obtain matte staple fibers with a length of 3 to 15 mm.

[0017] Furthermore, the pyrrolyl polyester monofilament method is: melt spinning the pyrrolyl polyester at a spinning speed of 800-1000 m / min and 270-280° C., and side-blowing cooling and solidification for 25-35 minutes at a wind speed of 0.9-1.3 m / s and 10-20° C. to obtain the pyrrolyl polyester monofilament.

[0018] Furthermore, the pyrrolyl polyester method is: 1H-pyrrole-3,4-dicarboxylic acid, 1,2,3-tribromopropane, and N,N-dimethylformamide are mixed in a mass ratio of 2.5:2:10~3.5:3:10, stirred at 150~250rpm for 10~20min, and then tetramethylguanidine with a mass of 1.1~1.3 times that of 2,4-dibromo-5-hydroxybenzaldehyde is added, and stirring is continued for 12~24h, and ethyl acetate is added until precipitation is complete, filtered, and vacuum dried at -0.08MPa and 60~70°C for 12~18h to obtain pyrrolyl polyester.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The invention prepares the impact-resistant base material from a matting agent and elastic polystyrene, and then mixes it with other additives to prepare the wear-resistant high-strength plastic with matting and impact-resistant effects.

[0021] Firstly, a matting agent is prepared from 1H-pyrrole-3,4-dicarboxylic acid, 1,2,3-tribromopropane and p-hydroxybenzaldehyde; after polycondensation of carboxyl groups in 1H-pyrrole-3,4-dicarboxylic acid and bromine groups in 1,2,3-tribromopropane, pyrrole-based polyester monofilaments are spun; during the self-spinning process of the pyrrole-based polyester monofilaments, tantalum ion irradiation is assisted to generate etchable latent tracks on the surface of the pyrrole-based polyester monofilaments; after etching by an alkali-alcohol mixed solution, irregular cone-shaped protrusions are formed on the fiber surface; and matting staple fibers are obtained by shearing. The staple fibers can be dispersed on The disordered distribution in the plastic overlaps with each other and cooperates with the irregular conical protrusions on its surface to construct a micro-nano rough plane, increasing the diffuse reflection of the plastic surface, thereby giving the plastic a matte effect; the pyrrole in the matte staple fiber and the formaldehyde in p-hydroxybenzaldehyde form a porphyrin structure that can absorb visible light. At the same time, p-hydroxybenzaldehyde self-polymerizes to form porous microspheres, further increasing the roughness of the fiber surface and enhancing the diffuse reflection of light. At the same time, the multi-aperture structure of the microspheres enhances the multiple reflections of light, thereby further enhancing the matte effect of the plastic.

[0022] Secondly, elastic polystyrene is prepared from N-allylmaleimide, styrene and 1,5-hexadiene; N-allylmaleimide, styrene and 1,5-hexadiene are polymerized by double bonds to prepare elastic polystyrene, forming a cross-linked network structure with polystyrene and N-allylmaleimide as hard phases and poly-1,5-hexadiene as soft phases, which can improve the impact resistance of plastics through the yield deformation effect of the soft phase and the rigid support effect of the hard phase; maleimide in elastic polystyrene reacts with furan in matting agent to form DA bonds to prepare impact-resistant base material, and when subjected to external stress, the stress is transmitted to the fibrous matting agent through elastic polystyrene, and the stress is diffused to the entire material through the matting agent, and at the same time, the rough surface and complex spatial structure of the matting agent improve the bonding force between the matting agent and the matrix through the mechanical meshing force of micro-pits and plastics and the synergistic effect of DA bonds, so that the impact resistance of the plastic is further improved. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the wear-resistant high-strength plastics prepared in the following examples are as follows:

[0025] Matting effect: Take the same size of the embodiment and the comparative example and test the gloss according to ASTMD523;

[0026] Impact resistance: The embodiment and the comparative example were subjected to pressure maintenance for 10 min at an injection temperature of 180 degrees Celsius, a mold temperature of 60 degrees Celsius, and a pressure of 5 GPa to obtain a notched impact strip with a length of 80 mm, a width of 10 mm, and a thickness of 2 mm; the impact strength of the notched impact strip was tested according to GB / T1843.

[0027] Example 1

[0028] (1) 1H-pyrrole-3,4-dicarboxylic acid, 1,2,3-tribromopropane and N,N-dimethylformamide were mixed in a mass ratio of 2.5:2:10, stirred at 150 rpm for 10 min, and then tetramethylguanidine (1.1 times the mass of 2,4-dibromo-5-hydroxybenzaldehyde) was added, and the stirring was continued for 12 h. Ethyl acetate was added until the precipitation was complete, filtered, and vacuum dried at -0.08 MPa and 60 ° C for 12 h to obtain pyrrole-based polyester; the pyrrole-based polyester was melt-spun at a spinning speed of 800 m / min and 270 ° C, and cooled and solidified by side blowing at a wind speed of 0.9 m / s and 10 ° C for 25 min to obtain pyrrole-based polyester monofilament;

[0029] (2) The pyrrolyl polyester monofilament rotating at 30 rpm was irradiated with tantalum ions at an irradiation density of 10 5 Tracks / cm 2 The irradiated pyrrolyl polyester monofilament was immersed in an alkali-alcohol mixture with a mass fraction of 10 times that of the pyrrolyl polyester monofilament for 10 minutes, wherein the mass ratio of the alkali-alcohol mixture was 10% sodium hydroxide solution and methanol was 1:1, and the monofilament was washed with deionized water until the pH value of the washing solution was 6. After drying at room temperature for 12 hours, the monofilament was sheared to obtain a matte staple fiber with a length of 3 mm.

[0030] (3) Mix the matte staple fiber, sodium acetate and deionized water in a mass ratio of 1:0.7:9, react at 95°C and 200 rpm for 4 hours, wash with deionized water 3 times, and dry at 45°C for 2 hours to obtain the pretreated staple fiber; mix the pretreated staple fiber, p-hydroxybenzaldehyde and pyridine in a mass ratio of 1:1:15, react at 200 rpm and 91°C for 25 hours, add 38% hydrochloric acid with a mass fraction of twice the mass of the pretreated staple fiber, ultrasonicate at a frequency of 30 kHz and 95°C for 30 minutes, wash with ethanol and deionized water 3 times in sequence, and dry at 50°C for 2 hours to obtain the matting agent;

[0031] (4) N-allylmaleimide, styrene, cyclohexane and butyl lithium were mixed in a mass ratio of 4:9:500:0.005, stirred at 200 rpm and 60°C for 30 min, then 1,5-hexadiene in an amount of 1.1 times the mass of N-allylmaleimide was added, and the reaction was continued for 60 min. Styrene in an amount of 4 times the mass of N-allylmaleimide and butyl lithium in an amount of 0.006 times the mass of N-allylmaleimide were added, and the reaction was continued at 200 rpm and 75°C for 30 min. Then, anhydrous ethanol in an amount of 0.01 times the mass of N-allylmaleimide was added, and the mixture was stirred at 100 rpm for 10 min, and then dried at 80°C for 6 h to obtain elastic polystyrene;

[0032] (5) Elastic polystyrene and matting agent are mixed in a mass ratio of 60:15, stirred at 150°C and 600 rpm for 6 hours, and then an additive mixture with a mass ratio of 1 times the mass of the matting agent is added. The mass ratio of aluminum oxide powder, stearic acid, triethyl phosphate, and tri(2,4-di-tert-butyl)phenyl phosphite in the additive mixture is 0.05:0.6:3:0.03. Stir at 100 rpm and 190°C for 2 hours, and extrude and granulate at 190-210°C to obtain a wear-resistant high-strength plastic.

[0033] Example 2

[0034] (1) 1H-pyrrole-3,4-dicarboxylic acid, 1,2,3-tribromopropane and N,N-dimethylformamide were mixed in a mass ratio of 3:2.5:10, stirred at 200 rpm for 15 min, and then tetramethylguanidine (1.2 times the mass of 2,4-dibromo-5-hydroxybenzaldehyde) was added, and the stirring was continued for 18 h. Ethyl acetate was added until the precipitation was complete, and the mixture was filtered and vacuum dried at -0.08 MPa and 65 °C for 15 h to obtain pyrrole-based polyester; the pyrrole-based polyester was melt-spun at a spinning speed of 900 m / min and 275 °C, and cooled and solidified by side blowing at a wind speed of 1.1 m / s and 15 °C for 30 min to obtain pyrrole-based polyester monofilament;

[0035] (2) The pyrrolyl polyester monofilament rotating at 40 rpm was irradiated with tantalum ions at an irradiation density of 10 6 Tracks / cm 2 The irradiated pyrrolyl polyester monofilament was immersed in an alkali-alcohol mixture with a mass fraction of 15 times that of the pyrrolyl polyester monofilament for 15 minutes, wherein the mass ratio of the alkali-alcohol mixture to the sodium hydroxide solution with a mass fraction of 10% and methanol was 1:1, and the monofilament was washed with deionized water until the pH value of the washing solution was 6.5. After drying at room temperature for 12 hours, the monofilament was sheared to obtain a matte staple fiber with a length of 9 mm.

[0036] (3) Mix the matte staple fiber, sodium acetate and deionized water in a mass ratio of 1:1.05:13.5, react at 100°C and 250rpm for 5h, wash with deionized water 4 times, and dry at 50°C for 3h to obtain the pretreated staple fiber; mix the pretreated staple fiber, p-hydroxybenzaldehyde and pyridine in a mass ratio of 1:2:20, react at 250rpm and 93°C for 30h, add 38% hydrochloric acid with a mass fraction of 3 times the mass of the pretreated staple fiber, ultrasonicate at a frequency of 35kHz and 100°C for 35min, wash with ethanol and deionized water 4 times in sequence, and dry at 55°C for 3h to obtain the matting agent;

[0037] (4) N-allylmaleimide, styrene, cyclohexane and butyl lithium were mixed in a mass ratio of 5:10:500:0.006, stirred at 250 rpm and 65°C for 40 min, then 1.3 times the mass of 1,5-hexadiene was added to the mixture, and the reaction was continued for 75 min. Then, 5 times the mass of styrene and 0.006 times the mass of butyl lithium were added to the mixture, and the reaction was continued at 250 rpm and 80°C for 40 min. Then, 0.012 times the mass of N-allylmaleimide was added to the mixture with anhydrous ethanol, and the mixture was stirred at 150 rpm for 15 min, and then dried at 85°C for 7 h to obtain elastic polystyrene.

[0038] (5) Elastic polystyrene and matting agent are mixed in a mass ratio of 70:15, stirred at 160°C and 700 rpm for 9 hours, and then an additive mixture 1.5 times the mass of the matting agent is added. The mass ratio of alumina powder, stearic acid, triethyl phosphate, and tri(2,4-di-tert-butyl)phenyl phosphite in the additive mixture is 0.1:0.7:4:0.03. Stir at 150 rpm and 200°C for 3 hours, and extrude and granulate at 190-210°C to obtain a wear-resistant high-strength plastic.

[0039] Example 3

[0040] (1) 1H-pyrrole-3,4-dicarboxylic acid, 1,2,3-tribromopropane and N,N-dimethylformamide were mixed in a mass ratio of 3.5:3:10, stirred at 250 rpm for 20 min, and then tetramethylguanidine (1.3 times the mass of 2,4-dibromo-5-hydroxybenzaldehyde) was added, and the stirring was continued for 24 h. Ethyl acetate was added until the precipitation was complete, and the mixture was filtered and vacuum dried at -0.08 MPa and 70 °C for 18 h to obtain pyrrole-based polyester; the pyrrole-based polyester was melt-spun at a spinning speed of 1000 m / min and 280 °C, and cooled and solidified by side blowing at a wind speed of 1.3 m / s and 20 °C for 35 min to obtain pyrrole-based polyester monofilament;

[0041] (2) The pyrrolyl polyester monofilament rotating at 50 rpm was irradiated with tantalum ions at an irradiation density of 10 7Tracks / cm 2 The irradiated pyrrolyl polyester monofilament was immersed in an alkali-alcohol mixture with a mass fraction of 20 times that of the pyrrolyl polyester monofilament for 20 minutes, wherein the mass ratio of the alkali-alcohol mixture was 10% sodium hydroxide solution and methanol was 1:1, and the monofilament was washed with deionized water until the pH value of the washing solution was 7. After drying at room temperature for 12 hours, the monofilament was sheared to obtain a matte staple fiber with a length of 15 mm.

[0042] (3) Mix the matte staple fiber, sodium acetate and deionized water in a mass ratio of 1:1.4:18, react at 105°C and 300 rpm for 6 hours, wash with deionized water 5 times, and dry at 55°C for 4 hours to obtain the pretreated staple fiber; mix the pretreated staple fiber, p-hydroxybenzaldehyde and pyridine in a mass ratio of 1:3:25, react at 300 rpm and 95°C for 35 hours, add 38% hydrochloric acid with a mass fraction of 4 times the mass of the pretreated staple fiber, ultrasonicate at a frequency of 40 kHz and 105°C for 40 minutes, wash with ethanol and deionized water 5 times in sequence, and dry at 60°C for 4 hours to obtain the matting agent;

[0043] (4) N-allylmaleimide, styrene, cyclohexane, and butyl lithium were mixed in a mass ratio of 6:11:500:0.007, stirred at 300 rpm and 70°C for 50 min, and then 1.5 times the mass of 1,5-hexadiene of N-allylmaleimide was added, and the reaction was continued for 90 min. Styrene of 6 times the mass of N-allylmaleimide and 0.006 times the mass of butyl lithium of N-allylmaleimide were added, and the reaction was continued at 300 rpm and 85°C for 50 min. Anhydrous ethanol of 0.014 times the mass of N-allylmaleimide was added, and the mixture was stirred at 200 rpm for 20 min, and then dried at 90°C for 8 h to obtain elastic polystyrene;

[0044] (5) Elastic polystyrene and matting agent are mixed in a mass ratio of 80:15, stirred at 170°C and 800 rpm for 12 h, and then an additive mixture twice the mass of the matting agent is added. The mass ratio of alumina powder, stearic acid, triethyl phosphate, and tri(2,4-di-tert-butyl)phenyl phosphite in the additive mixture is 0.15:0.8:5:0.03. The mixture is stirred at 200 rpm and 210°C for 4 h, and extruded and granulated at 190-210°C to obtain a wear-resistant high-strength plastic.

[0045] Comparative Example 1

[0046] The difference between Comparative Example 1 and Example 2 is that step (2) is different, and step (2) is changed to: cutting the pyrrolyl polyester monofilament to obtain a matte staple fiber with a length of 9 mm. The remaining steps are the same as those of Example 2.

[0047] Comparative Example 2

[0048] The difference between Comparative Example 2 and Example 2 is that there is no step (3), and step (5) is changed to: elastic polystyrene and matte staple fibers are mixed in a mass ratio of 70:15, stirred at 160° C. and 700 rpm for 9 hours, and then an additive mixture of 1.5 times the mass of the matting agent is added, wherein the mass ratio of aluminum oxide powder, stearic acid, triethyl phosphate, and tri(2,4-di-tert-butyl)phenyl phosphite in the additive mixture is 0.1:0.7:4:0.03, stirred at 150 rpm and 200° C. for 3 hours, and extruded and granulated at 190-210° C. to obtain a wear-resistant high-strength plastic. The remaining steps are the same as those in Example 2.

[0049] Comparative Example 3

[0050] The difference between Comparative Example 3 and Example 2 is that step (4) is different. Step (4) is changed to: N-allylmaleimide, styrene, cyclohexane and butyl lithium are mixed in a mass ratio of 5:10:500:0.006, stirred at 250 rpm and 65° C. for 115 min, styrene 5 times the mass of N-allylmaleimide and butyl lithium 0.006 times the mass of N-allylmaleimide are added, reacted at 250 rpm and 80° C. for 40 min, anhydrous ethanol 0.012 times the mass of N-allylmaleimide is added, stirred at 150 rpm for 15 min, and dried at 85° C. for 7 h to obtain elastic polystyrene. The remaining steps are the same as those of Example 2.

[0051] Comparative Example 4

[0052] The difference between Comparative Example 4 and Example 2 is that there are no steps (1) to (3), and step (5) is changed to: after the elastic polystyrene is stirred at 160° C. and 700 rpm for 9 hours, an additive mixture of 0.32 times the mass of the elastic polystyrene is added, wherein the mass ratio of aluminum oxide powder, stearic acid, triethyl phosphate, and tri(2,4-di-tert-butyl)phenyl phosphite in the additive mixture is 0.1:0.7:4:0.03, stirring at 150 rpm and 200° C. for 3 hours, extrusion granulation at 190-210° C., and a wear-resistant high-strength plastic is obtained. The remaining steps are the same as those in Example 2.

[0053] Comparative Example 5

[0054] The difference between Comparative Example 5 and Example 2 is that step (4) is different. Step (4) is changed to: styrene, cyclohexane and butyl lithium are mixed in a mass ratio of 10:500:0.006, stirred at 250 rpm and 65° C. for 40 min, 1,5-hexadiene in an amount of 0.65 times the mass of styrene is added, the reaction is continued for 75 min, styrene in an amount of 2.5 times the mass of styrene and butyl lithium in an amount of 0.003 times the mass of styrene are added, the reaction is continued at 250 rpm and 80° C. for 40 min, anhydrous ethanol in an amount of 0.06 times the mass of styrene is added, the mixture is stirred at 150 rpm for 15 min, and then dried at 85° C. for 7 h to obtain elastic polystyrene. The remaining steps are the same as those of Example 2.

[0055] Effect example

[0056] Table 1 below shows the performance analysis results of the wear-resistant high-strength plastics of Examples 1 to 3 and Comparative Examples 1 to 5 of the present invention.

[0057] Table 1

[0058]

[0059] From the comparison of the glossiness data of the embodiment and the comparative example in Table 1, it can be found that the matting effect of the plastic after adding the matting agent is significantly improved. After the pyrrolyl polyester monofilament is irradiated with tantalum ions during the self-rotation process, the matting staple fibers with irregular cone-shaped protrusions on the surface are obtained by etching and shearing with an alkali-alcohol mixture, which can be randomly dispersed in the plastic to construct a micro-nano rough surface, increase the diffuse reflection of light, and thus make the plastic have a matting effect. The p-hydroxybenzaldehyde further reacts with the matting staple fibers to generate a porphyrin structure, and self-polymerizes to form porous microspheres. The composite of porous microspheres and linear fibers further improves the unevenness of the plastic, and synergistically enhances the matting effect of the plastic with the light absorption of the porphyrin structure and the multi-reflectivity of the porous structure of the microspheres to enhance the light. From the comparison of the notched impact strength data of the embodiment and the comparative example in Table 1, it can be found that the matting effect of the plastic is significantly improved after adding the matting agent. It was found that the plastic has good impact resistance. Elastic polystyrene is prepared by polymerization of N-allylmaleimide, styrene and 1,5-hexadiene to form polystyrene. The yield deformation effect of the soft phase of poly1,5-hexadiene and the rigid support effect of polystyrene and polyN-allylmaleimide can improve the impact resistance of the plastic. The matting agent is dispersed in the elastic polystyrene. After the elastic polystyrene is subjected to force, the stress is transferred to the matting agent. The matting agent is used to disperse the stress to the entire material, thereby further improving the impact resistance of the plastic. In addition, the elastic polystyrene and the matting agent are chemically cross-linked through DA bonds, and the rough surface and complex spatial structure of the matting agent improve the bonding force between the matting agent and the matrix through the mechanical meshing force of the micro-pits and the plastic, thereby enhancing the impact resistance of the plastic.

[0060] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing wear-resistant high-strength plastic, characterized in that: The method comprises the following preparation steps: (1) 1H-pyrrole-3,4-dicarboxylic acid, 1,2,3-tribromopropane and N,N-dimethylformamide were mixed in a mass ratio of 3:2.5:10, stirred at 200 rpm for 15 min, and then tetramethylguanidine (1.2 times the mass of 2,4-dibromo-5-hydroxybenzaldehyde) was added, and the stirring was continued for 18 h. Ethyl acetate was added until the precipitation was complete, and the mixture was filtered and vacuum dried at -0.08 MPa and 65 °C for 15 h to obtain pyrrole-based polyester; the pyrrole-based polyester was melt-spun at a spinning speed of 900 m / min and 275 °C, and cooled and solidified by side blowing at a wind speed of 1.1 m / s and 15 °C for 30 min to obtain pyrrole-based polyester monofilament; (2) The pyrrolyl polyester monofilament rotating at 40 rpm was irradiated with tantalum ions at an irradiation density of 10 6 Tracks / cm 2 The irradiated pyrrolyl polyester monofilament was immersed in an alkali-alcohol mixture with a mass fraction of 15 times that of the pyrrolyl polyester monofilament for 15 minutes, wherein the mass ratio of the alkali-alcohol mixture to the sodium hydroxide solution with a mass fraction of 10% and methanol was 1:1, and the monofilament was washed with deionized water until the pH value of the washing solution was 6.

5. After drying at room temperature for 12 hours, the monofilament was sheared to obtain a matte staple fiber with a length of 9 mm. (3) Mix the matte staple fiber, sodium acetate and deionized water in a mass ratio of 1:1.05:13.5, react at 100°C and 250rpm for 5h, wash with deionized water 4 times, and dry at 50°C for 3h to obtain the pretreated staple fiber; mix the pretreated staple fiber, p-hydroxybenzaldehyde and pyridine in a mass ratio of 1:2:20, react at 250rpm and 93°C for 30h, add 38% hydrochloric acid with a mass fraction of 3 times the mass of the pretreated staple fiber, ultrasonicate at a frequency of 35kHz and 100°C for 35min, wash with ethanol and deionized water 4 times in sequence, and dry at 55°C for 3h to obtain the matting agent; (4) N-allylmaleimide, styrene, cyclohexane and butyl lithium were mixed in a mass ratio of 5:10:500:0.006, stirred at 250 rpm and 65°C for 40 min, then 1.3 times the mass of 1,5-hexadiene was added to the mixture, and the reaction was continued for 75 min. Then, 5 times the mass of styrene and 0.006 times the mass of butyl lithium were added to the mixture, and the reaction was continued at 250 rpm and 80°C for 40 min. Then, 0.012 times the mass of N-allylmaleimide was added to the mixture with anhydrous ethanol, and the mixture was stirred at 150 rpm for 15 min, and then dried at 85°C for 7 h to obtain elastic polystyrene. (5) Elastic polystyrene and matting agent are mixed in a mass ratio of 70:15, stirred at 160°C and 700 rpm for 9 hours, and then an additive mixture 1.5 times the mass of the matting agent is added. The mass ratio of alumina powder, stearic acid, triethyl phosphate, and tri(2,4-di-tert-butyl)phenyl phosphite in the additive mixture is 0.1:0.7:4:0.

03. Stir at 150 rpm and 200°C for 3 hours, and extrude and granulate at 190-210°C to obtain a wear-resistant high-strength plastic.

Citation Information

Patent Citations

  • Delustering master batch for plastic and preparation method thereof

    CN114591554A

  • High-elastic wear-resistant fabric and preparation method thereof

    CN114990898A

  • Complete extinction polyester drawing yarns and preparation method thereof

    WO2020134495A1